Gastric leiomyoma and hyperplastic polyposis coli in a patient with multiple cutaneous and uterine leiomyomatosis - Serra, D (2014)
BACKGROUND: Cutaneous leiomyomatosis has been associated with multiple uterine myomas and, more recently, with germline heterozygous mutations of the FH gene and certain types of renal cancer. Despite the growing amount of knowledge concerning this genodermatosis, its clinical spectrum remains incompletely characterized. OBJECTIVE: We report the observation of a patient with multiple cutaneous and uterine leiomyomatosis (MCUL) with unusual gastrointestinal manifestations. METHODS AND RESULTS: A gastric leiomyoma was diagnosed on a 38-year-old female MCUL patient on endoscopy performed because of mild dyspepsia. Furthermore, routine colonoscopy disclosed hyperplastic polyposis. Genetic testing revealed a previously not reported mutation of the FH gene. CONCLUSION: Gastrointestinal lesions such as the present ones are frequently asymptomatic and probably underdiagnosed. As the phenotypical spectrum associated with mutations of the FH gene keeps expanding, clinicians should keep in mind that, besides renal cancer, other unexpected tumors could also arise in this setting.